(untitled) (Вестник КазНУ. Серия Экономическая, 2017)
In this article, the problem of effective conducting budgeting as one of management tools which costs in the center of attention of scientists as for today the organizations quite often practice creation of budgets is considered. However, now scientists did not give unambiguous definition and purpose of budgeting and therefore the budgeting system seldom brings to the entities desirable result. The purpose of this article to analyse efficiency of budgeting which showed that it is possible to allocate basic reasons of this problem: lack of the accurate purpose of a budgeting system in case of its implementation at the entity; a gap between strategic objectives of the entity and the purposes of a budgeting system; lack of support of implementation process of strategy by budgeting. As a result of our research we found out that enhancement of a budgeting system by means of implementation of an algorithm of creation of budgets in it gives the chance of increase in efficiency of implementation process of strategy of the entity as: orients it to implementation process of strategy of the entity; the ordered system of creation of budgets will concentrate on value increase of the entity.